Identification of a ERCC5 c.2333T>C (L778P) Variant in Two Tunisian Siblings With Mild Xeroderma Pigmentosum Phenotype - Chikhaoui, Asma; Elouej, Sahar; Nabouli, Imen; Jones, Meriem; Lagarde, Arnaud; Ben Rekaya, Meriem; Messaoud, Olfa; Hamdi, Yosr; Zghal, Mohamed; Delague, Valerie; Levy, Nicolas; De Sandre-Giovannoli, Annachiara; et al. (Frontiers in Genetics, 2019)
Xeroderma pigmentosum (XP) is a rare autosomal recessive disorder due to a defect in the nucleotide excision repair (NER) DNA repair pathway, characterized by severe sunburn development of freckles, premature skin aging, and susceptibility to develop cancers at an average age of eight. XP is an example of accelerated photo-aging. It is a genetically and clinically heterogeneous disease. Eight complementation groups have been described worldwide. In Tunisia, five groups have been already identified. In this work, we investigated the genetic etiology in a family with an atypically mild XP phenotype. Two Tunisian siblings born from first-degree consanguineous parents underwent clinical examination in the dermatology department of the Charles Nicolle Hospital on the basis of acute sunburn reaction and mild neurological disorders. Blood samples were collected from two affected siblings after written informed consent. As all mutations reported in Tunisia have been excluded using Sanger sequencing, we carried out mutational analysis through a targeted panel of gene sequencing using the Agilent HaloPlex target enrichment system. Our clinical study shows, in both patients, the presence of achromic macula in sun exposed area with dermatological feature suggestive of Xeroderma pigmentosum disease. No developmental and neurological disorders were observed except mild intellectual disability. Genetic investigation shows that both patients were carriers of an homozygous T to C transition at the nucleotide position c.2333, causing the leucine to proline amino acid change at the position 778 (p.Leu778Pro) of the ERCC5 gene, and resulting in an XP-G phenotype. The same variation was previously reported at the heterozygous state in a patient cell line in Europe, for which no clinical data were available and was suggested to confer an XP/CS phenotype based on functional tests. This study contributes to further characterization of the mutation spectrum of XP in consanguineous Tunisian families and is potentially helpful for early diagnosis. It also indicates that the genotype-phenotype correlation is not always coherent for patients with mild clinical features. These data therefore suggest that targeted NGS is a highly informative diagnostic strategy, which can be used for XP molecular etiology determination.